Oral acute toxicity of imidacloprid, thiamethoxam and clothianidin in eared doves: a contribution for the risk assessment of neonicotinoids in birds - Addy Orduna, Laura (2018)
Neonicotinoids have recently been demonstrated to cause direct negative impacts on birds from North America and Europe. To further understand the impact of these compounds on bird species and to improve risk assessment capacities, the current study determined the acute toxicities of imidacloprid, clothianidin, and thiamethoxam formulations on South American eared doves (Zenaida auriculata). Insecticides were administered by gavage to adult doves to determine median lethal doses (LD50) according to a standardized sequential procedure. The acute toxicity of formulated imidacloprid (LD50=59mgactive ingredient, a.i./kg bodyweight, b. w.) was much higher than that of the tested formulations of clothianidin (LD50 = 4248 mg a.i./kg b.w.) and thiamethoxam (LD50 = 4366 mg a.i./kg b.w.). Imidacloprid also differed from the other two neonicotinoids in terms of the onset and intensity of intoxication signs and the times of death and recovery. All three insecticides induced a reduction in food consumption that led to body weight loss. An average weight dove of 127 g would obtain a dose equivalent to the LD50 of imidacloprid by consuming 1.7 g of treated sorghum seeds. As eared doves offered non-treated sorghum seeds 5 h per day consumed on average 6.4±1.8 g (mean±S.D.), it is concluded that these doves could feasibly be exposed to lethal doses in the field. Thiswork is the first to describe intoxication signs and report oral neonicotinoid LD50s in a wild South-American bird species.